Understanding common law legislation drafting and interpretation - Bennion, Francis Alan Roscoe (Oxford : Oxford University Press, 2009)
Common law largely operates through statutes enacted by democratic legislature, and these mainly fall to be construed according to a uniform system of rules, presumptions, principles and canons evolved over centuries by common law judges.
Originally published: 2001.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Common law; Statutes; Law -- Interpretation and construction